Analyzing the Motives of US Foreign Policy in Iraq - Dina Yulianti; Arfin Sudirman; Francesca Klarensia Angela (Yayasan Ilomata, 2023)
Twenty years have passed since the US occupation of Iraq, yet the deployment of the US military in the Middle Eastern country remains today. Initially, the US argued that the primary aim for invasion was the disarmament of the mass weapons (WMD). Further on, they claimed that the intervention was to help establish the Iraq democracy. The final justification for the troops to stay was to combat ISIS (Islamic State of Iraq and Syria). This raises the question, what are the true motives of the US foreign policy in Iraq? This research was conducted using a qualitative method by analyzing textual data from the previous studies, official documents, and media reports. The data are analyzed using foreign policy theory related to national interests. The findings of this study indicate that the main motive why the US military continue to exist in Iraq is to maintain its power and hegemony in the region. In line with that, the US also has economic motives, such as oil and arms business.